Building children's character through play and competition methods at Hidayatul Mubtadi'in islamic kindergarten - Ramawati, Rosalia; Muthohar, Sofa (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: Character development requires an interesting and relevant approach by developing an integrative model based on games and competitions that also instills Islamic values. Objective: This research aims to analyze the effectiveness of a game-based learning model combined with Islamic values in shaping the character of young children Methods: The research used a descriptive qualitative approach through observation, in-depth interviews, and documentation at the Hidayatul Mubtadi'in Islamic Kindergarten which was analyzed using Thematic Analysis. The research subjects consisted of 2 teachers and 41 students who were divided into two groups per class. Result: The learning model applied was proven to strengthen the character of cooperation, honesty and sportsmanship through game rules and reflection of Islamic values. The integration of the values ​​of trust, manners and caring also improves children's social skills. The main contribution of this research is the preparation of a structured model that combines games, competition, and the internalization of Islamic values, which has not previously been researched much in the PAUD context. Conclusion: This integrative model is effective in cultivating children's character that is in line with Islamic values, with the role of the teacher as the main facilitator. The research recommends further development in broader learning contexts and media.